PROS AND NEGATIVES OF TRANSFERRING AGRICULTURAL LAND TO OTHER LAND CATEGORIES (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
The article analyzes the positive and negative aspects of the process of transferring agricultural land to other land categories (land conversion) on a scientific and theoretical basis. The importance of land conversion from the perspective of efficient use of land resources, economic development, environmental sustainability, and social consequences is revealed. Also, scientific conclusions are given on the problems associated with changing the land category in the conditions of Uzbekistan and their mitigation.